The Low-Risk Anomaly: Evidence From The Thai Stock Market - Saengchote, Kanis (Asian Academy of Management (AAM), 2017)
In many developed countries, low-risk stocks tend to earn superior risk-adjusted returns compared to high-risk stock. Using data on the Stock Exchange of Thailand between 2004 and 2015, this paper shows that the abnormal returns associated with investing in low-beta stocks are signifcant and robust. The zero-cost portfolio that longs low-beta stocks and shorts high-beta stocks delivers monthly four-factor alpha of 1.26%. This paper provides suggestive evidence that, in addition to leverage constraints, the low-risk anomaly can be caused by institutional designs that favour stocks that are index constituents.